Sociodemographic factors associated with health-related quality of life in UK healthcare workers: a cross-sectional study - Christopher A. Martin; Rebecca F. Baggaley; Lucy Teece; Daniel Pan; Joshua Nazareth; Luke Bryant; Carol Rivas; Katherine Woolf; Manish Pareek; The UK-REACH study collaborative group (BMC Medicine)
Abstract Background Healthcare workers’ (HCW) health and wellbeing directly affect patient care, yet little is known about their health-related quality of life (HRQoL) in the United Kingdom (UK). Using data from a nationwide study conducted during the COVID-19 pandemic in the UK (December 2020 to March 2021), we evaluated self-reported HRQoL among HCWs and its variation by sociodemographic characteristics. Methods HRQoL was measured using the five-dimension-five-level EuroQoL (EQ-5D-5L) questionnaire, covering five health dimensions. We explored differences in reported HRQoL by age, sex, Index of Multiple Deprivation (IMD) quintile, ethnicity, migration status and occupational group. Each HRQoL dimension was collapsed into a binary outcome (any problems versus none) and associations analysed using logistic regression. We also examined EQ-5D-5L visual analogue scale (VAS) scores using linear regression. Results Among 12,026 HCWs, 75.9% were female, 26.7% overseas-born and 29.9% from non-White ethnic groups. HCWs reported high levels of pain/discomfort and anxiety/depression (43.7% and 46.1% reporting at least slight problems, respectively). Women were more likely than men to report problems across all EQ-5D-5L dimensions. Reporting health problems increased with increased deprivation. Asian overseas-born and Black HCWs were less likely than White UK-born HCWs to report anxiety/depression. Compared to the Medical group, other HCW types reported more problems with pain/discomfort (32.2% Medical, 55.4% Nursing, 45.4% Allied Health Professionals, 49.8% Ambulance groups) and anxiety/depression (36.8% Medical, 52.9% Nursing, 50.5% Ambulance groups). Nurses and ambulance workers showed particularly high rates of pain/discomfort. Overall, all HCWs reported more problems with anxiety/depression, usual activities and pain/discomfort than the Medical group. Similar associations were demonstrated in a parallel analysis of VAS scores. Conclusions In the largest study of HRQoL in HCWs to date, EQ-5D-5L VAS scores were lower than those reported elsewhere for the general UK population (for ages up 45 years), with high levels of anxiety/depression and pain/discomfort and substantial heterogeneities across EQ-5D-5L dimensions by sex, occupation and deprivation level. However, HCWs’ circumstances during the COVID-19 pandemic may have influenced their reporting of HRQoL. Our findings highlight the need for further research to understand the causes of lower HRQoL, particularly among women and certain occupational groups, and to inform targeted interventions.